Cover Feature: Competing Roles of Two Kinds of Ligand during Nonclassical Crystallization of Pillared‐Layer Metal‐Organic Frameworks Elucidated Using Microfluidic Systems (Chem. Eur. J. 41/2020). Issue 41 (9th July 2020) - Tanaka, Yoko; Kitamura, Yu; Kawano, Ryuji; Shoji, Kan; Hiratani, Moe; Honma, Tetsuo; Takaya, Hikaru; Yoshikawa, Hirofumi; Tsuruoka, Takaaki; Tanaka, Daisuke
Abstract : Microfluidic systems are efficient tools for elucidating the non‐equilibrium state on the crystallization of multi‐component metal–organic frameworks (MOFs). The understanding of the crystallization mechanism makes it possible to predict the synthesis conditions. Based on the experimental analysis using microflow reactors, nonclassical crystallization processes are proposed, involving two kinds of intermediate states and the competing roles of two kinds of ligand which promote or suppress nucleation. More information can be found in the Full Paper by R. Kawano, D. Tanaka, et al. on page 8889 .